Root Canal Transportation in Canals Joining together: Assessed by Cone-Beam Computed Tomography - Neda Naghavi; Mina Zarei; Maryam Gharechahi; Ali Bagherpour; Zahra Owsati (Mashhad University of Medical Sciences, 2018)
Introduction: Statement of the Problem: Cleaning and shaping are regarded as the most important aspects of root canal therapy and prerequisite for the success of endodontic treatment. Apical transportations can jeopardize the outcome of treatment due to the significant decrease in the sealing ability of root filling material. The purpose of this study was to evaluate transportation in type II canals with two preparation techniques. Materials and Method: Twenty lower first molars were selected and divided into 2 groups of 10. In the first group, the lingual canal of the mesial root was selected as the main canal and prepared up to the WL. The other canal (buccal) was prepared up to the juncture point. In the second group, both canals in the mesial root were prepared up to the working length. The amount and direction of canal transportation in each group were determined in five sections from 2 mm above the juncture point of the canals to 2 mm below the juncture point in 1-mm increments. Results: There were no significant differences between the two techniques in causing transportation in both buccolingual and mesiodistal directions in each increments (P>0.05). Conclusion: Both preparation techniques caused transportation in both mesiodistal and buccolingual directions.